Una óptica a las declaraciones tributarias de la cooperativa exportadora Mussa Export en el año 2015 y 2016. - Proaño Gutama, Anabel Carolina (2018)
The present work called "An optics to the tax returns of the Cooperativa Mussa Export in 2015 and 2016", aims to analyze the declarations made by the Mussa Export cooperative in 2015 and 2016. For the execution of this work, it was organized, first indicating the object of our study that are the tax declarations, externalizing that optics have this topic at a global level, as well as being important for a group of companies such as the corporate sector, the effects of the causes that exist in the Mussa Export cooperative, for which we set ourselves the objective: To analyze the tax declarations presented by the Mussa Export cooperative, by comparing them, object of study, and the investigation in the regulation and tax regulations in force in Ecuador, for an objective argumentation of these and to prevent future contraventions. In the second part we have the contextualization of relevant issues that help us argue in an objective way the analysis of tax returns to the cooperative through background, literature and laws, which complements the research together with its third arises the methodological process for research of this work, by interviewing the manager, accountant and accounting assistant, survey of a sample of the population of accountants in the province and the observation guide as investigative data collection techniques for the presentation of data required in the cooperative. In its fourth and final part of the work, by analyzing the information found in scientific journals and laws such as tax regulations, and the data found with the research techniques, an analysis is delivered based on the statements made in the Cooperativa Mussa Export , in the year 2015-2016. With this work, it was evidenced the important role that lies in the efficiency of the accountant in the preparation of tax returns, since these are not managed under the regulations in the time required, and in addition to the constant communication that must be carried out with society, you can avoid many contraventions with the Internal Revenue Service, avoid unnecessary expenses in fines that can be avoided by making timely tax returns and communicating the effects of a tax violation and jointly process solutions for the good of the company. The analysis of compliance with tax obligations in the Mussa Export cooperative, leads me to the conclusion that generating a tax debt and take time to fix it, leads to unnecessary spending that increases more and more, which could be avoided by hiring an accountant efficient, and in the same way the partners do not skimp on optimal staff costs and investing in tools such as the accounting computer system, in improving the cooperative and its partners. It is important to highlight that companies or taxpayers in general must take into account that just as the Internal Revenue Service, every time, it increases its control mechanisms to the operations carried out by taxpayers in Ecuador, it must also organizations, taxpayer , improve its policies of organization, control, such as internal audits, training of personnel, investment of IT tools in this globalized world, where statements are made via the Internet and information is increasingly automated.